Climate women in the workplace: Integrative literature review (Research, Society and Development, 2021)
The present study aimed to investigate the scientific evidence about the influences of climacteric illness on the daily work of women who have experienced this phase. This is an integrative literature review conducted between May and September of June 2020, with publications between 2010 and 2020, in Portuguese, English and Spanish languages that addressed the topic in the databases PUBMED, Virtual Health Library and Latin American Literature. The results of the studies show the climacteric period as a complex phase in the perception of women and point to the difficulty in living with the symptoms in the workplace. They also pointed out that in this scenario they infer an increase in the intensity of the symptoms. They also approach the quality of life of women and issues related to sex life, highlighting the negative way they experience in this phase. The female population's knowledge about the climacteric period is still deficient and/or scarce, and the symptoms of this phase can affect the ability of some women to perform work activities. This condition reflects in weaknesses regarding their self-perception for the performance of their tasks. And it is concluded that the study contributes with current evidence enabling the creation of strategies for professionals in assisting the demands of women. Greater clarification is needed so that women have an understanding of the physiological phase of climacteric.